2019
DOI: 10.1111/ijfs.14104
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical CO2 extraction of grape seeds oil: scale‐up and economic analysis

Abstract: This work presents a scale-up and feasibility study for the establishment of supercritical CO 2 extraction plants to produce grape seeds oil. The scale-up factors are determined using experimental and modelling results based on seeds from six grape cultivars over 2 harvest years. The purchased cost of the production plant is estimated using 'the six-tenth rule' from the cost of a pilot scale unit. The results indicate that, at the current minimum retail selling price of extra virgin grape seeds oil, the propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Although SFE is not the most efficient method for obtaining larger amounts of phenolic compounds and antioxidant activity of the samples, it is observed that this method provides greater selectivity to obtain p-coumaric acid and formononetin in grape seed oil samples. It is noteworthy that one of the main aspects that should be considered in the SFE is the choice of operating conditions in the extraction process [22,69], as this may provide an additional advantage to conventional methods such as for example clean technology and more selective methodology [69].…”
Section: Antioxidant Activity and Phenolic Compoundsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although SFE is not the most efficient method for obtaining larger amounts of phenolic compounds and antioxidant activity of the samples, it is observed that this method provides greater selectivity to obtain p-coumaric acid and formononetin in grape seed oil samples. It is noteworthy that one of the main aspects that should be considered in the SFE is the choice of operating conditions in the extraction process [22,69], as this may provide an additional advantage to conventional methods such as for example clean technology and more selective methodology [69].…”
Section: Antioxidant Activity and Phenolic Compoundsmentioning
confidence: 99%
“…It is noteworthy that the quality and composition of the extracts and products obtained from plant samples are fundamentally related to the extraction technique employed [14,22]. Grape seed oil is most commonly extracted by the pressing process or through processes that use organic solvents (Bligh and Dyer or Soxhlet).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Supercritical CO 2 extraction method, a new green technology for the extraction and separation of oil or bioactive compounds, has several advantages. For example, it has a high extraction efficiency, a lower operation temperature, a shorter extraction time and the use of lower amounts of extraction solvents compared with conventional extraction methods (Soxhlet extraction and maceration) (Conte et al, ; Duba & Fiori, , ; Freitas, Dariva, Jacques, & Caramão, ; Mustafa & Turner, ). The supercritical CO 2 extraction of tea seed oil has been investigated by several researchers to study the effects of parameters such as extraction pressure, extraction temperature, extraction time, and cosolvents on the yield and composition of the extracted oil (Rajaei et al, ; Xu, Zhong, Liu, Long, & Li, ; Zhou, Gu, & Gu, ).…”
Section: Introductionmentioning
confidence: 99%
“…(Duba & Fiori, 2015;Martinez, 2008). Based on previous studies, this supercritical CO 2 extraction method could decrease the degradation of bioactive compounds, leading to a final extracted product without toxic residuals (Benito-Román, Rodríguez-Perrino, Sanz, Melgosa, & Beltrán, 2018;da Silva et al, 2016;Duba & Fiori, 2019;Mariod, Matthaus, & Ismail, 2011).…”
mentioning
confidence: 99%